THE MEANING OF TUDUNG MANTO FOR THE MALAY DAIK - Febby Febriyandi Y.S (Pusbindiklat - LIPI, 2011)
Tudung Manto is one of the main items for Malay women traditional clothing in the village of Daik Malay, Linga District, Riau Islands Province. This research tries to understand the meaning contained in the Tudung Manto by using qualitative method and the interpretivisme symbolic paradigm. This study shows that motif of tudung manto is avehicle used by the Malays Daik to bring the concept of value altruistic, glory, unity, and integrity, obedience to God, Sincerity and honesty, brotherhood, orderly, harmonious, abstinence give up, to maintained the reputation, keep the peace, wealth and prosperity, the concept of human, social stratification, as well as the concept of Malay identity.